Explore flowchart and pseudocode concepts in algorithms and programming - Tarsini, Iin; Anggraeni, Riska (Indonesian Journal of Multidisciplinary Science, 2024)
Programming algorithms are a class of mathematical algorithms that are widely used in computer science and engineering. They are used to solve problems involving mathematical calculations, but in their implementation, algorithms do not always handle complex calculations, especially when genetic algorithms are often used. This article uses the method of literature study or literature review to evaluate several studies related to the topic discussed, especially in introducing the basic concepts of programming algorithms, especially for beginners, focusing on the basic understanding required. The research includes a review of algorithmic concepts, algorithm notation, characteristics, properties, and the basic structure of algorithm learning, along with the steps of implementing programming algorithms. The conclusion of this article is that learning basic programming algorithms is an essential necessity for anyone who wants to get started in the world of programming.